KONTEMPLASI TINDAK TUTUR DIREKTIF DALAM KITAB SUCI TRIPITAKA DHAMMAPADA SYAIR DANDAVAGGA - Tantra, Manggala Wiriya; Suryosumunar, John Abraham Ziswan; Siswadi, Gede Agus (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This research aims to describe the use of directive speech acts found in the Dandavagga Chapter of the Tripitaka Dhammapada Holy Book. This research data was taken from various sources of speech act literature studies and the Tripitaka holy book, namely the Dhammapada Chapter of Dandavagga which contains 13 holy verses. The methodology used uses a qualitative approach. The results of the research found based on in-depth discussion and analysis illustrate the pattern of trends in the type of directive speech, namely advice is found most often at 7, warning at 4, command at 1, invitation at 0, and prohibition at 1. The directive speech act of advice is the most dominant speech act. In the Dandavagga poetry, it is perpendicular to the stated aim, namely providing advice to mankind, emphasizing how important it is to avoid evil acts, avoid inappropriate actions that can lead to punishment, and achieve the essence of life, namely happiness.